2022
DOI: 10.1007/s10561-022-10010-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound enhances immunomodulation and facilitates osteogenesis of human periodontal ligament stem cells by inhibiting the NF-κB pathway

Abstract: Human periodontal ligament stem cells (hPDLSCs) are vital in cellular regeneration and tissue repair due to their multilineage differentiation potential. Low intensity pulsed ultrasound (LIPUS) has been applied for treating bone and cartilage defects. This study explored the role of LIPUS in the immunomodulation and osteogenesis of hPDLSCs. hPDLSCs were cultured in vitro, and the effect of different intensities of LIPUS (30, 60, and 90 mW/cm 2 ) on hPDLSC v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
(67 reference statements)
1
3
0
Order By: Relevance
“…It has been demonstrated that ALP activity in osteoblasts increases from day 5 after daily US stimulation, which can be an indicative of enhanced osteogenesis [22,41]. Also, hPLFs have been reported to synthetize more ALP up to seven days after US stimulation [42,43]. In our study, the ALP expression was constant throughout the experiment for all conditions, with no statistically significant differences being observed between stimulated cells and the control group over three days of daily stimulation.…”
Section: Discussionsupporting
confidence: 49%
“…It has been demonstrated that ALP activity in osteoblasts increases from day 5 after daily US stimulation, which can be an indicative of enhanced osteogenesis [22,41]. Also, hPLFs have been reported to synthetize more ALP up to seven days after US stimulation [42,43]. In our study, the ALP expression was constant throughout the experiment for all conditions, with no statistically significant differences being observed between stimulated cells and the control group over three days of daily stimulation.…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, this study limits the direct applicability of the results to adult humans or skeletally mature individuals. Another study identified the role for LIPUS in immunomodulation and osteogenesis in hPDLSCs and showed that LIPUS enhanced the immunomodulation and osteogenic differentiation of hPDLSCs by inhibiting the NF-κB signaling pathway in a dose-dependent manner ( 48 ).…”
Section: Mechanisms Involved In the Biological Effects Of Lipus On St...mentioning
confidence: 99%
“…LIPUS could facilitate the osteogenesis and microvascular formation of periodontal ligament stem cells [123,124]. Stimulated by LIPUS, autologous ADSC transplantation with fibrin can lead to superior bone-tendon healing quality in the patella-patellar tendon junctions when compared with LIPUS or ADSCs alone.…”
Section: Bone-ligament or Bone-tendon Repairmentioning
confidence: 99%